1996
DOI: 10.1046/j.1471-4159.1996.66041717.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Age Alters Transbilayer Fluidity and Cholesterol Asymmetry in Synaptic Plasma Membranes of Mice

Abstract: Previous studies examining age differences in membrane fluidity and cholesterol content have reported on the average or total change in membrane structure, respectively. However, a membrane consists of an exofacial leaflet and a cytofacial leaflet that differ in fluidity and cholesterol distribution. The purpose of the present experiments was to determine fluidity and cholesterol distribution of the exofacial and cytofacial leaflets of brain synaptic plasma membranes (SPMs) from 3-4-, 14-15-, and 24-25-month-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 18 publications
6
110
1
Order By: Relevance
“…5b). In fact, the concentration of cholesterol in the cytofacial leaflet of brain synaptic plasma membrane is lower in aged people (60), and A␤ cannot insert into the membrane containing less cholesterol (61). Once A␤ exits the membrane and enters into the extracellular solution, the segment of residues 29-40 has a high tendency to form short ␤-sheets (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5b). In fact, the concentration of cholesterol in the cytofacial leaflet of brain synaptic plasma membrane is lower in aged people (60), and A␤ cannot insert into the membrane containing less cholesterol (61). Once A␤ exits the membrane and enters into the extracellular solution, the segment of residues 29-40 has a high tendency to form short ␤-sheets (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…in (12,144,145). DHE revealed that the cytofacial leaflet of plasma membranes from L-cell fibroblasts (12,24,146,147), erythrocytes (144), and brain synaptosomes (145,(148)(149)(150)(151). While other methods (filipin staining, exchange, cholesterol oxidase accessibility, neutron diffraction, etc) have also been used to measure transbilayer cholesterol distribution, many have significant limitations including accessibility of membrane cholesterol (filipin, cholesterol oxidase), production of a potential perturbant (cholesterol oxidase produces cholesterone), and poor dynamic resolution (neutron diffraction) (rev.…”
Section: Dhe Architecture In Purified Biological Membranesmentioning
confidence: 99%
“…While measurements of transbilayer sterol distribution by different methods may therefore not necessarily agree, multiple methods (DHE, NBD-cholesterol quenching, and exchange assays) indicate that the cytofacial leaflet of erythrocytes has more cholesterol than the exofacial leaflet (144,152). Likewise, several methods (DHE, cholesterol oxidase) indicate that the synaptosomal plasma membrane has more cholesterol in the cytofacial leaflet than the exofacial leaflet (12,145,(148)(149)(150). The transbilayer distribution of sterol is a major determinant of the transbilayer fluidity gradient present in these membranes, the cytofacial cholesterol-rich leaflet is more rigid (less fluid) than the relatively cholesterol-poor exofacial leaflet (rev.…”
Section: Dhe Architecture In Purified Biological Membranesmentioning
confidence: 99%
See 2 more Smart Citations